The move: program development from in-person to online. (25th November 2019) - Price, Philip; Harrison, Natalie J.; Cundiff, Nicole L.
A graduate level program in supply chain management that transitioned from a face-to-face instructional format to a fully online program is examined in detail using case study methodology. A framework is presented to demonstrate the program elements to be analysed and addressed when strategically aligning courses to enhance student learning in online teaching. Pedagogical factors to be considered when transferring an educational program to an online degree are discussed with emphasis on generally overlooked factors. Additionally, stakeholder assessment and buy-in demonstrates how course topics and essential design elements, as well as program layout, can be informed and enhance by influential stakeholders of the program. Applied detailed examples are given to support utilisation of the framework. This case study adds to the literature by providing a comprehensive guide and useful templates to online program development and design.